2021
DOI: 10.4081/ejh.2021.3306
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity and a new staining method of monocarboxylate transporter 1 located in endothelial cells of cerebral vessels of human brain in distinguishing cerebral venules from arterioles

Abstract: Distinguishing brain venules from arterioles with arteriolosclerosis is less reliable using traditional staining methods. We aimed to immunohistochemically assess the monocarboxylate transporter 1 (MCT1), a specific marker of venous endothelium found in rodent studies, in different caliber vessels in human brains. Both largeand small-caliber cerebral vessels were dissected from four autopsy donors. Immunoreactivity for MCT1 was examined in all autopsied human brain tissues, and then each vessel was identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…6 10 Anti-MCT1 immunohistochemical staining, a sensitive and reliable method for distinguishing cerebral venules from arterioles, combined with anti-αSMA, was used in our study to overcome these problems. 8 We found that although the severity of arteriolosclerosis significantly increased with venular collagenosis across the brain regions, an inverse severity distribution was found in 20%-30% of cases. These data suggest that, despite some shared risk factors, the mechanisms underlying the development arteriolosclerosis and venous collagenosis might differ.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…6 10 Anti-MCT1 immunohistochemical staining, a sensitive and reliable method for distinguishing cerebral venules from arterioles, combined with anti-αSMA, was used in our study to overcome these problems. 8 We found that although the severity of arteriolosclerosis significantly increased with venular collagenosis across the brain regions, an inverse severity distribution was found in 20%-30% of cases. These data suggest that, despite some shared risk factors, the mechanisms underlying the development arteriolosclerosis and venous collagenosis might differ.…”
Section: Discussionmentioning
confidence: 62%
“… 6 10 Anti-MCT1 immunohistochemical staining, a sensitive and reliable method for distinguishing cerebral venules from arterioles, combined with anti-αSMA, was used in our study to overcome these problems. 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the severity of arteriolosclerosis and venular collagenosis, 2400 µm × 3800 µm single images were captured randomly in anti-αSMA and anti-MCT1 immunostained sections to differentiate between arterioles and venules, and the corresponding visual elds on the delineated images were subsequently captured in adjacent Masson's trichrome sections to assess the severity. For arteriolosclerosis evaluation, based on our previous report [25], vessels from 10 to 200 µm in diameter that showed negative immunolabeling for MCT1 and positive immunolabeling for αSMA were considered arterioles. According to the Vascular Cognitive Impairment Neuropathology Guidelines (VCING)[26], arteriolosclerosis was graded according to severity using histological semiquantitative scales ranging from 0 to 3 (0 = normal, 1 = mild changes, 2 = moderate changes, and 3 = severe changes).…”
Section: Evaluations Of Arteriolosclerosis and Venular Collagenosismentioning
confidence: 99%